The Effectiveness of Warm Compresses in HNP Patients to Reduce Pain Levels in the Eri Soedewo Pavilion Room, V Floor, Gatot Soebroto Army Hospital - M.Pd (Letnan Kolonel Ckm NRP 33812), Memed Sena Setiawan, S.Kp, (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
Background: HNP is a condition in which the annulus fibrosus and nucleus pulposus protrude into the spinal canal. The basis of HNP is the process of intervertebral disc degeneration so that it often occurs in the third and fifth decades. Postoperative is the period after surgery. In general, post-operative patients will experience complaints of pain on a mild to severe scale, if the pain is not treated properly it can interfere with the patient's activities. Objective: This case study aims to reduce the level of pain consisting of pharmacological (analgesic therapy) and non-pharmacological actions. One of the non-pharmacological actions that can reduce pain is warm compresses. Method: This case study uses a descriptive method in the form of a single case study conducted on one patient with a medical diagnosis of Hernia Nucleus Pulposus who was treated on the 5th Floor of the Eri Sadewo Pavilion, RSPAD Gatot Soebroto, using data collection techniques, namely observation, interviews, and physical examination. The patient was given a non-pharmacological intervention of warm compresses. Implementation was carried out for 3x24 hours. Results: The evaluation showed that after being given a warm compress, the patient said the pain was still felt, the pain scale was 4, the intervention was continued independently. Conclusion: After conducting a case study that shows that the application of warm compresses to post-operative HNP patients has an effect on reducing the pain scale and providing comfort to patients